(untitled) - Noble, David F. (New York, 1977)
The New Republic "One of the best books of the last decade....It has that rare balance: quiet, cumulative power with bolts of lightning every few pages."--William Appleman Williams, Oregon State University "One of the outstanding works of radical social science of the 1970s.
Keywords: Công nghệ,Technology; Khía cạnh xã hội,Social aspects; Hoa Kỳ,United States